The Socio Economic Life, Poverty And Trafficking Case Study In Tomohon City, North Sulawesi Province - Jola S. Kalang; Elsje Hanna Lintong; Deisy A.P.J. Pangkey; Jeffry W.L. Gumerung; Rieneke R. Kalalo (Budapest International Research and Critics University, 2022)
The problem of socio-economic life towards poverty and trafficking has become a social disease of the community. It needs to get a serious concern because poverty is a complex problem involving various aspects such as the right to get food, health, education, and employment. Those aspects can trigger woman trafficking. The woman trafficking issue is actually not a new thing, but until the present, it still becomes a public concern, especially for the government officials who are often bothered by the actions of irresponsible people who incidentally take advantage of the poor economic conditions of the community. Based on these problems, this research focused on the phenomenon of socio-economic problems of the poor and woman trafficking. The method used was descriptive with secondary data which was then analyzed qualitatively. The results showed that in trafficking cases, the women were forced to be sex workers in other areas, international workers disguised themselves as dancers, and so on. A lot of girls became the victims of deception by criminals and became slaves in modern times. Efforts have been made by both the central and regional governments through exclamations and regulations in Regional Regulations on the prevention and control of human trafficking, especially woman trafficking, as well as organizations such as Non-Governmental Organizations, gender awareness, Information Center for Women's Protection, Bureau of Women's Empowerment, through seminars and workshops which resulted in a recommendation for regulations to protect girls and women.